2021
DOI: 10.1002/mmce.22613
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of annular ring microstrip antenna using conformal mapping

Abstract: Annular ring microstrip antenna (ARMA) is investigated here using the conformal mapping technique. The annular ring shape is transformed into a rectangular one using conformal mapping. The wave equation is solved in the transformed domain to find the approximate solution of the eigenfunction and eigenvalue for different TMmnp modes. Resonant frequency, internal field patterns, input impedance and far‐field radiation patterns are investigated. Internal field patterns are shown for the first few modes using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Laura has also investigated flower shape fluid waveguides using CMT in 1967 16 . CMT has also been used to investigate many MAs like Pentagonal MA, 17 spiral MA, 18 and annular MA 19 . It is found that no theoretical investigation has been reported on FSMA using CMT.…”
Section: Introductionmentioning
confidence: 99%
“…Laura has also investigated flower shape fluid waveguides using CMT in 1967 16 . CMT has also been used to investigate many MAs like Pentagonal MA, 17 spiral MA, 18 and annular MA 19 . It is found that no theoretical investigation has been reported on FSMA using CMT.…”
Section: Introductionmentioning
confidence: 99%